Overweight and obesity among adolescents: health-conscious behaviours, acceptance, and the health behaviours of their parents - Anna Lewandowska; Grzegorz Rudzki; Tomasz Lewandowski; Anna Bartosiewicz; Michał Próchnicki; Aleksandra Stryjkowska-Góra; Barbara Laskowska; Małgorzata Sierpińska; Sławomir Rudzki; Sergii Pavlov (BMC Public Health)
Abstract Background Obesity is a nutritional diseases, one of the most significant of the 21st century, that has grown to epidemic proportions. Overweight and obesity, once considered a problem in high-income countries, now affect low- and middle-income countries, especially in urban areas. Overweight and obesity rates among children and adolescents are constantly rising. The main cause of obesity and overweight is a lack of energetic balance between consumed and expended calories. Obesity in children is associated with an increased risk of non-communicable diseases, but in addition to somatic problems, it also causes negative psychosocial effects. The aim of the study was to analyse factors leading to overweight and obesity in young people and assess the impact of the health behaviours of parents on their children’s health. Methods A cross-sectional study was conducted per the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. A convenience sampling method was used, and the study was conducted among adolescents with excess body weight and their parents, as well as adolescents with normal body weight. The study used a questionnaire, body mass index assessment, physical activity assessment, and a health behaviour inventory. Results The study included 340 people, 170 with excess body weight, and 170 from the control group. The average age in the study group was 14.58 years, with a standard deviation of 2.72. The age of parents of children with excess body weight was between 20 and 50 years. Among parents of overweight or obese children, more than half were overweight (54%), and another 27% were obese. 41% of respondents with eating disorders assessed their knowledge of the causes, effects, and methods of preventing overweight and obesity as average. In the group of overweight or obese respondents, 84% prefer passive leisure time. People who are not overweight mostly accept their appearance (66%), while people with excess body mass do not accept their appearance (63%). The surveyed parents usually perceived their knowledge of proper nutrition as good (75%). Conclusions A relationship exists between normal weight, overweight or obesity, and a sense of happiness. The highest sense of happiness was reported by people who were not overweight.